Demography and Health of Twins in Sub-Saharan Africa - (:unkn) unknown (My University, 2020)
Twin births present a public health problem, as twins are more fragile than singletons and have a higher mortality rate than singletons. The frequency of twin births in sub-Saharan Africa averaged 17‰ in 2010, which is the highest in the world. In addition, the under-5 mortality of twins in sub-Saharan Africa is three times higher than that of singletons. This thesis aims to measure the frequency of twin births in sub-Saharan Africa and to study their excess mortality. Therefore, we examine the evolution of attitudes and behaviours towards twins; the variations of the twinning rate in space and time (1986-2016), its factors, as well as its prospects in a context where Assisted reproductive technology is still underdeveloped; and the evolution of the twins' excess mortality during the period 1986-2016 and its factors. The quantitative part of the thesis analyses data from national surveys (in particular demographic and health surveys) and Health and Demographic Surveillance System (HDSS), while the qualitative part analyses interviews concerning attitudes and behaviour towards twins. In total, we use data from 174 national surveys from 42 countries; 23 HDSSs; and 94 semi-directive interviews conducted in Burkina Faso and Senegal. The main results confirmed the high twinning rate in sub-Saharan Africa, but it has a rather slow temporal dynamic. In terms of health, our results have shown a significant decrease in child mortality on the continent over the last decades, but the excess mortality of twin children remains very high. In addition, our qualitative analyses have shown that the contemporary sub-Saharan twin is culturally shared between tradition and modernity.
Keywords: African Research